Chronic kidney disease is potentially an independent prognostic factor for death in Stevens-Johnson syndrome and toxic epidermal necrolysis patients - Rattanakaemakorn, Ploysyne; Palakornkitti, Pasita; Pinyowiwat, Prinpat; Jedee, Phatphitcha; Thadanipon, Kunlawat (Frontiers in Medicine, 2022)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are mucocutaneous conditions associated with high mortality and morbidity. Although several prognostic factors have been proposed, some may have yet to be identified. A 14-year retrospective cohort study of patients with SJS/TEN was conducted at a university-based hospital in Bangkok, Thailand, to explore additional prognostic factors for mortality of patients with SJS/TEN. Medical records of all patients aged ≥18 years who were diagnosed with SJS, SJS-TEN overlap, or TEN between 2007 and 2020 were reviewed. Univariate and multivariate analyses were performed to examine associations between death and potential prognostic factors. A total of 76 patients with a mean age of 52 years were enrolled. Among them, 46, 15, and 15 patients were diagnosed with SJS, SJS-TEN overlap, and TEN, respectively. Overall, 10 patients deceased, marking a mortality rate of 13.2%. Based on an algorithm for assessment of drug causality for epidermal necrolysis, drug was the major cause of disease (96.1%). Allopurinol and trimethoprim/sulfamethoxazole were the most frequent culprit drugs. Univariate analysis revealed 9 prognostic factors related to death, i.e., age, malignancy, chronic kidney disease (CKD), coronary artery disease, heart rate >120 beats/min, diagnoses of SJS-TEN overlap and TEN, blood urea nitrogen (BUN) >10 mmol/L, hemoglobin <10 g/dL, and serum albumin <2 g/dL. Causality with regard to drug, drug notoriety, time interval from drug intake to onset of reaction, and timing of culprit drug withdrawal were not significantly associated with death. Four independent prognostic factors for mortality were identified from multivariate analysis, i.e., TEN (risk ratio [RR] 8.29, 95% confidence interval [CI]: 2.71-25.38), malignancy (RR 3.34, 95% CI: 1.68-6.69), BUN >10 mmol/L (RR 3.02, 95% CI: 1.28-7.14), and early-stage CKD (RR 4.81, 95% CI: 2.49-9.28). Our findings suggest that CKD is an independent prognostic factor for mortality of patients with SJS/TEN besides those from the SCORTEN.